Big George Foreman [videorecording (Blu-Ray)] - Tillman, George, 1969-; Baldwin, Frank (Screenwriter); Gordon, Dan, 1947-; Davis, Khris; Mathews, Jasmine; Jones, Sullivan (Narrator); Gilliard, Larry; Magaro, John, 1983-; Trammell, Sam, 1971-; Sohn, Sonja; Whitaker, Forest (Sony Pictures Home Entertainment, 2023)
"Fueled by an impoverished childhood, George Foreman channels his anger into becoming the World Heavyweight Champion, and later survives a near-death experience that takes him from the ring to the pulpit. But when he sees his community struggle, he reclaims his title, becoming the oldest and most improbable heavyweight champion ever" --Container.